Prevalence and influencing factors of pandemic fatigue during normalized COVID-19 containment among the public in China: an online cross-sectional survey - Yanni LIU; Yanhua HAO; Ziyu WANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo investigate the prevalence of pandemic fatigue and its associates during the period of normalized containment of coronavirus diease 2019 (COVID-19) among the public in China. MethodsThrough an online survey platform 'Wenjuanxing' and with self-designed questionnaires on demographics, COVID-19-related risk perception, protective behaviors, negative emotion, and pandemic fatigue, we conducted a self-administered survey during February - March 2021 among web users aged 18 years and above in five provincial level administrative divisions across China. The collected data were analyzed with descriptive statistics, chi-square test and logistic regression analysis. Results Of 4 325 participants with eligible responses, 1 082 (25.0%) reported pandemic fatigue symptoms; 1 844 (42.6%) reported only having psychosomatic fatigue and 1 050 (24.3%) only having information fatigue. The results of logistic regression analysis revealed that the participants with following characteristics were more likely to have pandemic fatigue symptoms: with poor health status (odds ratio [OR] = 1.838, 95% confidence interval [ 95%CI]: 1.575 - 2.144), having a higher perceived susceptibility to COVID-19 (OR = 1.435, 95%CI: 1.236 - 1.667), having a lower perceived controllability of COVID-19 (OR = 1.760, 95%CI: 1.495 - 2.070), and with highly negative emotion (OR = 3.493, 95%CI: 2.987 - 4.086). Conclusion Pandemic fatigue symptoms were prevalent during the period of COVID-19 containment and the symptoms were associated with self-reported health status, perceived controllability and susceptibility of COVID-19, and negative emotion among adult web users in China.